Localized Scleroderma, Systemic Sclerosis and Cardiovascular Risk: A Danish Nationwide Cohort Study - Jeanette Halskou Hesselvig; Kristian Kofoed; Jashin J. Wu; Lene Dreyer; Gunnar Gislason; Ole Ahlehoff (Medical Journals Sweden, 2017)
Recent findings indicate that patients with systemic sclerosis have an increased risk of cardiovascular disease. To determine whether patients with systemic sclerosis or localized scleroderma are at increased risk of cardiovascular disease, a cohort study of the entire Danish population aged ≥ 18 and ≤ 100 years was conducted, followed from 1997 to 2011 by individual-level linkage of nationwide registries. Multivariable adjusted Cox regression models were used to estimate the hazard ratios (HRs) for a composite cardiovascular disease endpoint. A total of 697 patients with localized scleroderma and 1,962 patients with systemic sclerosis were identified and compared with 5,428,380 people in the reference population. In systemic sclerosis, the adjusted HR was 2.22 (95% confidence interval 1.99-2.48). No association was seen between patients with localized scleroderma and cardiovascular disease. In conclusion, systemic sclerosis is a significant cardiovascular disease risk factor, while patients with localized scleroderma are not at increased risk of cardiovascular disease.